Hierarchical N-body simulations in haskell - Martínez López, Pablo E. (1997)
Functional Programming was historically considered a toy for re searchers but recent developments in the eld show that its area of ap plication is wider The Hierarchical N Body method is an iterative method used in as trophysics to simulate the gravitational evolution of collisionless matter in order to understand the formation of galaxies In this work functional programming is used as a tool for the descrip tion and prototipation of the Hierarchical N Body method in an attempt to show that it is a suited tool for expressing problems mantaining a good understanding of them and allowing a great degree of abstraction and generalization and with a reasonable e ciency for a prototype .